(untitled) (Revista Logos Ciencia & Tecnología, 2019)
Silage is a process used to preserve food from anaerobic fermentation and lactic acid production. However, its effectiveness depends on factors such as the substrate and the dominant microorganisms. The objective of this work was to determine the effect of a bacterial inoculant on the compositional and microbiological quality of silage based on mulberry (Morus alba L.) and elderberry (Sambucus nigra L.). The plant material was chopped (3-5 cm) and mixed in a 50-50 ratio with liofast® inoculant (15%, 10%) and fermented for 28 days. Greater volumetric loss (dry matter) and growth of enterobacteria (190 × 10-9 CFU.g-1) was observed with the use of the inoculant (15%).